AN ANALYISIS OF THE RELATIONSHIPS AMONG RELIGIOUSITY, MOTIVATION, AND ENGLISH COMPETENCE OF THE STUDENTS OF ENGLISH STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, SRIWIJAYA UNIVERISTY - HARISWAN PUTERA JAYA (Sriwijaya University Learning and Education International Conference, 2016)
This study is aimed at finding out the religiousity level, English learning motivation, and English competency of the students of English Education Study Program, Faculty of Teacher Training and Education, Sriwijaya University as well as relationships among the three variables. This is a descriptive and correlational study in which the findings aree statistically described and correlated. It is found that the students‟ level of religiousity is high. The students‟ level of learning motivation is also high. The students‟ English competency is 45.7 % is in Low Intermediate category, 24.9 % was in Elementary category, 19.9 % was in High Intermediate category, and 9.8% was in Advanced category. There is a signficant relationship between religiousity and learning motivation. However, there is no significant relationship between religiousity and English competency and there is no significant relationship between learning motivation and English competency either.